Deconstructing Exceptional Responses to Immune Checkpoint Inhibition in Recurrent or Metastatic Head and Neck Carcinoma: A Site-Specific Clinical–Biological Synthesis - Giovanni Motta; Piero Giuseppe Meliante; Pasquale Capasso; Francesco Chiari; Giuseppe Tortoriello (Cancers, 2026)
Background: Recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC) is an aggressive malignancy with a historically poor prognosis. Although immune checkpoint inhibitors (ICIs) targeting the PD-1/PD-L1 axis have established a new first-line standard of care, durable clinical benefit is restricted to a minority of patients, while primary or acquired resistance remains a major clinical challenge. This narrative review aims to provide a conceptual clinical–biological synthesis of immunotherapy in R/M HNSCC through an anatomical and biomarker-driven lens, with a focus on characterizing potential shared features of “exceptional responders”. Methods: A targeted narrative literature search was conducted across PubMed/MEDLINE and to identify key clinical trials and representative clinical reports of exceptional response to ICIs in R/M HNSCC. The literature was not systematically synthesized to construct a conceptual clinical–biological framework of response and resistance. Results: Landmark clinical data confirm durable survival benefits with frontline pembrolizumab-based regimens in selected PDL-1 positive populations compared to historical chemotherapy. Qualitative appraisal of illustrative cases and translational cohorts suggests a potential biological hypothesis: exceptional responders, defined as patients achieving unexpected, multi-year complete radiological, pathological, or metabolic remissions, often align with a favorable confluence of a pre-existing “hot” or inflamed tumor microenvironment, preserved antigen presentation machinery, and elevated antigenic novelty driven by viral oncoproteins (HPV, EBV) or high mutational/indel burdens. Conversely, primary and acquired resistance are conceptually associated with defects in antigen processing, immunosuppressive cellular barriers, and alternative immune checkpoints. Conclusions: Immunotherapy has fundamentally transformed R/M HNSCC management, yet exceptional single-agent responses remain rare. Rather than a definitive or proven biological biomarker, the proposed blueprint represents an integrative hypothesis highlighting the complex interplay of baseline immune inflammation, genomic features, and viral drivers. Translating these observations into broader clinical benefit will require validated biomarker-driven personalization and rationally designed combination regimens.